Shakespeare en prison : le cas d’Avignon - Florence March (Sillages Critiques)
This essay offers to explore the structural link between three historical counter-spaces : prison, Shakespeare’s Elizabethan public theatre and the Avignon Festival. It will first deal with the decisive encounter of Shakespeare’s drama with prison in Avignon’s Papal Palace in 1947 – an encounter that acts as a catalyst for the festival’s ethos and aesthetics. The focus will then shift to the festival’s partnership with Le Pontet penitentiary. Launched in 2004 by Hortense Archambault and Vincent Baudriller, it was continued and developed by Olivier Py, who founded a theatre workshop for the inmates. By doing so, he re-engaged with the festival’s ethos, which promoted democratic theatre as a source of social cohesion in the aftermath of the Second World War. As in 1947, Shakespeare plays a major role in implementing the festival’s sociopolitical and artistic project with Le Pontet penitentiary. In this programme, which, just like the festival, foregrounds Shakespeare as the most often performed playwright, prison becomes a laboratory for theatre, and for Shakespeare’s drama in particular, whereas Shakespeare in his turn becomes a laboratory for revisiting the prison system.